COMING IN RUSSIAN CAPITAL INTO TURKISTAN DURING XIX-XX CENTURY (World Bulletin of Management and Law, 2023)
According to following article, types of craftsmanship and taken taxes, coming in Russian capital, how the industry plays an essential role in country, enables you to learn more in-depth details about role of domestic trade. As such, this article talks about the opinions and comments are given about a national bourgeoisie that got rich from industry